Directory of expertise Universiti Teknologi MARA - UiTM, Pejabat Perhubungan Korporat & Alumni (Pejabat Perhubungan Korporat & Alumni, Universiti Teknologi MARA, 2002)
UiTM has indeed come a long way since it began in 1956 as a training center whose main task was to educate ruval youths in commerce and cottage industries. Today, UiTM has expanded its wings and new courses have emerged to meet current needs of the ever-changing world. With the introduction of new courses, it becomes critical that new and advanced knowledge is developed through research and consultancy. It is with this in mind that the Bureau of Research and Consultancy at UiTM was set up and given the responsibility to coordinate research and consultancy efforts among our large pool of academics who are scattered throughout the country. The Directory of Expertise' is one of UiTM s efforts to document the vast array of our academic and field expertise, be it in Science and Technology or in the Social Sciences. This is a way of extending our hands to industries to share our expertise with the world and to form strategic alliances that can be of mutual benefit to all. The Directory provides a listing of our academics and their area of expertise and subsequently, their research interests can be used as guides for those requiring services from these experts. As a university whose main existence rest in ensuring the success of our nation, UiTM is ever ready to share our knowledge. It is therefore our aim that this 'Directory of Expertise^ will serve as a link between the academics and others who share common visions of achieve global success insyaAllah.